Development of Scientific-Based Interactive Powerpoint Media to Improve Process Skills of Elementary School Students - AgustinKartika Putri; PuspitaAri Metalin Ika (International Conference on Elementary Education, 2022)
The problem of applying process skills is that students only gain theoretical knowledge and without direct experience. So that students only listen to explanations from the teacher without carrying out meaningful learning activities that build students’ new knowledge and experiences. The purpose of this research is to develop and test scientific-based interactive powerpoint media to improve the process skills of elementary school students. The research and development method used is the ADDIE Model which consists of 5 (five) stages, namely analyzing, designing, developing, implementing, and evaluating. The research sample used was fourth grade students in 2 (two) elementary schools in Trenggalek Regency. Data collection techniques used observation sheets and process skills questionnaires. While the data analysis technique used to analyze the research data is the paired sample t-test. The result of the research conducted is that Scientific-Based Interactive Powerpoint Media is effective for Improving Process Skills of Elementary School Students and there are differences in student’s process skills before and after the effective use of Scientific-Based Interactive Powerpoint Media. The conclusion is that scientifically based interactive powerpoint media is able to solve students’ problems, namely the low student process skills.